3D imaging options and ultrasound contrast agents for the ultrasound assessment of pediatric rheumatic patients - Madej, Tomasz (J Ultrason, 2013)
The application of 3D imaging in pediatric rheumatology helps to make the assessment of inflammatory changes more objective and to estimate accurately their volume and the actual response to treatment in the course of follow-up examinations. Additional interesting opportunities are opened up by the vascularity analysis with the help of power Doppler and color Doppler in 3D imaging. Contrast-enhanced ultrasound examinations enable a more sensitive assessment of the vascularity of inflamed structures of the locomotor system, and a more accurate analysis of treatment's effect on changes in vascularity, and thereby the inflammation process activity, as compared to the classical options of power and color Doppler. The equipment required, time limitations, as well as the high price in the case of contrast-enhanced ultrasound, contribute to the fact that the 3D analysis of inflammatory changes and contrast-enhanced ultrasound examinations are not routinely applied for pediatric patients.